History in popular literature and textbooks for Xhosa schools, 1850-1950s (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The challenges of the contemporary demands for the decolonisation history in South African schools and universities require careful attention to the background of history education in our context. This article explores traces of that heritage as it influenced Xhosa language schools in the Eastern Cape during the first half of the twentieth century. Through the examination of the writing of Xhosa history by local scholars it demonstrates a rich tradition of writing that has to date been largely neglected by historians, and presents the potential challenge of this work for an understanding of identity and patriotism both then and now. Through a preliminary examination of school textbooks of the time, with specific reference to the Lovedale Press Stewart Xhosa Readers, I offer suggestions for future research that might be able to inform contemporary debates.
Keywords: Colonial education; History curriculum; History in Xhosa schools; Xhosa historiography; History textbook publishing